2021
DOI: 10.3389/fonc.2021.598226
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Methylenetetrahydrofolate Reductase C677T and A1298C Polymorphism on High-Dose Methotrexate-Related Toxicities in Pediatric Non-Hodgkin Lymphoma Patients

Abstract: PurposeThis retrospective study aimed to investigate the relationships between the methylenetetrahydrofolate reductase (MTHFR) C677T/A1298C and high-dose methotrexate (HD-MTX)-related toxicities in pediatric non-Hodgkin lymphoma (NHL) patients.Patients and MethodsWe reviewed the medical records of 93 NHL patients aged under 18 years who received HD-MTX therapy at the dose of 5 g/m2 with 24-h infusion at Sun Yat-sen University Cancer Center between 2014 and 2019.ResultsThere were 61 males and 32 females, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Thus, mutant genes are considered to induce a protective effect against mucosal damage, whereas wild-type genes are more likely to cause mucosal damage ( 39 ). In contrast, some studies also reported that C677T mutant genes are strongly associated with grade III or higher mucosal toxicity, thereby causing oral mucositis ( 28 , 29 , 40 ). In the present study, patients with the CT+TT mutant phenotype were more prone to mucosal damage in the high-risk group, but no correlation was observed in the low- and intermediate-risk groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, mutant genes are considered to induce a protective effect against mucosal damage, whereas wild-type genes are more likely to cause mucosal damage ( 39 ). In contrast, some studies also reported that C677T mutant genes are strongly associated with grade III or higher mucosal toxicity, thereby causing oral mucositis ( 28 , 29 , 40 ). In the present study, patients with the CT+TT mutant phenotype were more prone to mucosal damage in the high-risk group, but no correlation was observed in the low- and intermediate-risk groups.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, mutant genes are considered to induce a protective effect against mucosal damage, whereas wildtype genes are more likely to cause mucosal damage (39). In contrast, some studies also reported that C677T mutant genes are strongly associated with grade III or higher mucosal toxicity, thereby causing oral mucositis (28,29,40).…”
Section: Discussionmentioning
confidence: 99%
“…32 Our study focused on exploring different genetic polymorphisms than those commonly analyzed in the context of chemo-induced OM, which are usually related to drug metabolism. [14][15][16] To our knowledge, this is the first study investigating rs4880, rs7943316, rs1800629, and rs1800795 in a group of pediatric cancer patients with OM since it was not possible to obtain information about the distribution of these polymorphisms in other pediatric populations presenting this outcome. This demonstrates the importance of more studies in this area.…”
Section: Group Imentioning
confidence: 99%
“…Single-nucleotide polymorphisms (SNPs) in genes involving drug metabolism (ABCC2, rs717620; MTHFR, rs1801133; ABCG2 rs2231137) and cell signaling pathways (miR-1206, rs2114358) have been associated with the incidence of chemo-induced OM in pediatric blood cancer patients. [14][15][16][17] However, there are no reports on the relation between SNPs in genes involving antioxidant enzymes and chemo-induced OM in any population. Regarding polymorphisms in cytokine genes in the same context, reports are limited to studies involving adults.…”
Section: Introductionmentioning
confidence: 99%
“…Studies addressing genetic markers such as single nucleotide polymorphisms (SNPs) in the context of oral mucositis in oncopaediatric patients have already been conducted in China (Lu et al, 2021), the Netherlands (Den Hoed et al, 2015; Gutierrez‐Camino et al, 2017; Oosterom, Berrevoets, et al, 2018), Mexico (Ruiz‐Argüelles et al, 2007) and Turkey (Bektaş‐Kayhan et al, 2012), among others. We are the only group to date to conduct studies of this nature in Brazil (Coêlho et al, 2022; Viana Filho et al, 2021).…”
Section: Introductionmentioning
confidence: 99%